2018
DOI: 10.1016/j.jnutbio.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Common gut microbial metabolites of dietary flavonoids exert potent protective activities in β-cells and skeletal muscle cells

Abstract: Flavonoids are dietary compounds with potential anti-diabetes activities. Many flavonoids have poor bioavailability and thus low circulating concentrations. Unabsorbed flavonoids are metabolized by the gut microbiota to smaller metabolites, which are more bioavailable than their precursors. The activities of these metabolites may be partly responsible for associations between flavonoids and health. However, these activities remain poorly understood. We investigated bioactivities of flavonoid microbial metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 52 publications
9
53
0
Order By: Relevance
“…5-Phenylvaleric acid, hippuric acid and homovanillic acid improved GSIS in beta cells more effectively than EC at concentrations up to 100 µM [ 40 ]. In addition to stimulating beta cell function, the microbial metabolites enhanced glucose utilization in skeletal muscle [ 40 ].…”
Section: Antidiabetic Effects Of Flavan-3-ols: In Vitro and In Vivmentioning
confidence: 99%
“…5-Phenylvaleric acid, hippuric acid and homovanillic acid improved GSIS in beta cells more effectively than EC at concentrations up to 100 µM [ 40 ]. In addition to stimulating beta cell function, the microbial metabolites enhanced glucose utilization in skeletal muscle [ 40 ].…”
Section: Antidiabetic Effects Of Flavan-3-ols: In Vitro and In Vivmentioning
confidence: 99%
“…Ex vivo studies utilizing mouse serum and cardiovascular cells has been employed previously, and were used as a model for our unique approach (Petersen et al 2018). As mentioned previously, there is evidence that flavanol microbial metabolites (rather than native flavanols) may be primarily responsible for the bioactivities of these compounds in peripheral tissues due to their predominance in circulation, however, studies to date have been limited to in vitro models using purified single sources of flavanol microbial metabolites or basic mixtures of chemically synthesized compounds (Fernandez-Millan et al 2014;Bitner et al 2018). The present study design allowed for the generation of physiologically relevant mixtures of native flavanols and flavanol microbial metabolites for use in subsequent cell culture models, while also demonstrating the active role of the gut microbiome in the generation of flavanol microbial metabolites with bioactivities potentially more potent than native compounds in some cases.…”
Section: Characteristics Of Cell Modelsmentioning
confidence: 99%
“…Flavanol metabolites (representative structures in Figure 1) are readily absorbed into circulation and are excreted in the urine (Fernandez-Millan et al 2014;. While research has traditionally focused on the bioactivities of native flavanols in foods, the microbial metabolites may possess significant bioactivities as well (Monagas et al 2010;Fernandez-Millan et al 2014;Esposito et al 2015;Bitner et al 2018). The potential for flavanol microbial metabolites to confer benefits for the host is being explored (Aura 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bitner et al reported that hippuric acid and homovanillic acid, as well as the phenylvaleric acid 5-phenylvaleric acid, more effectively enhanced glucose-stimulated insulin secretion (GSIS) in beta cells than (−)-epicatechin at concentrations between 5 and 100 µM (hippuric acid between 5 and 50 µM) [38]. Contrary to (−)-epicatechin, the microbial metabolites enhanced GSIS without enhancing beta cell mitochondrial respiration or increasing expression of mitochondrial electron transport chain components [38]. In addition to the stimulation of beta cell function, the microbial metabolites stimulated glucose utilization in skeletal muscle and they preserved mitochondrial function after insulation [38].…”
Section: Biological Properties Of Flavan-3-ol Microbial Metabolitesmentioning
confidence: 99%